Effects of copper and copper oxide nanoparticles on cyanobacterium Nostoc linckia: an experimental study - Cepoi, Liliana; Rudi, Ludmila; Chiriac, Tatiana; Valuta, Ana; Codreanu, Svetlana; Mitina, Tatiana; Codreanu, Liviu (Frontiers in Microbiology, 2025)
IntroductionCopper nanoparticles (CuNPs) and copper oxide nanoparticles (CuONPs) are increasingly explored for their biological interactions with various organisms, including cyanobacteria, due to their unique properties and potential applications. This study investigates the effects of CuNPs and CuONPs on the cyanobacterium Nostoc linckia (Roth) Born et Flah CNMN-CB-03, focusing on biomass accumulation, biochemical content, pigment composition, and microscopic structural changes.MethodsNostoc linckia cultures were exposed to CuNPs and CuONPs at concentrations ranging from 0.1 to 30 mg/L. The impact on biomass, protein, pigment, lipid content, malondialdehyde (MDA) levels, and bioaccumulation of copper was assessed, alongside microscopic analysis to observe any structural modifications in trichomes.ResultsThe effects of CuNPs and CuONPs on Nostoc linckia were distinct. Under high concentrations of CuNPs exposure, reductions in biomass, protein content, and pigments were observed, whereas lipid and MDA content increased significantly. Similarly, CuONPs caused a marked increase in lipid and MDA levels, suggesting oxidative stress despite the comparatively moderate alterations in other biochemical parameters. Both nanoparticle types, however, caused notable bioaccumulation of copper and structural modification in Nostoc linckia cells expressed in trichome fragmentation, chromaticity changes, and variations in heterocyst numbers and size in treated samples.ConclusionCuNPs and CuONPs exhibit differential effects on Nostoc linckia, influencing biochemical composition, pigment profiles, and cellular structure. These findings contribute to understanding nanoparticle interactions with cyanobacteria and highlight the distinct impact of nanoparticle composition on microbial systems.